The Impact of Farming Mitigation Measures on Ammonia Concentrations and Nitrogen Deposition in the UK - Matthieu Pommier; Jamie Bost; Andrew Lewin; Joe Richardson (Atmosphere)
Ammonia (NH3) is an important precursor to airborne fine particulate matter (PM2.5) which causes significant health issues and can significantly impact terrestrial and aquatic ecosystems through deposition. The largest source of NH3 emissions in the UK is agriculture, including animal husbandry and NH3-based fertilizer applications. This study investigates the impact of mitigation measures targeting UK NH3 emissions from farming activities, focusing on their implications for air quality and nitrogen deposition in 2030. A series of mitigation scenarios—low2030, medium2030, and high2030—were developed through engagement with stakeholders, including farmers, advisers, and researchers, and their impact was modelled using the CMAQ air quality model. These scenarios represent varying levels of the uptake of mitigation measures compared to a baseline (base2030). The results indicate that reductions in total NH₃ emissions across the UK could reach up to 13% under the high2030 scenario (but reaching nearly 20% for some regions). These reductions can lead to significant decreases in NH₃ concentrations in some parts of the UK (up to 22%, ~1.2 µg/m3) but with a mean reduction of 8% across the UK. However, the reductions have a limited effect on fine ammonium particulate (<semantics><msubsup>NH4+</msubsup></semantics>) concentrations, achieving only modest reductions of up to 4%, with mean reductions of 1.6–1.9% due to a NH3-rich atmosphere. Consequently, the mitigation measures have minimal impact on secondary inorganic aerosol formation and PM2.5 concentrations, aligning with findings from other studies in Europe and beyond. These results suggest that addressing the primary sources of PM2.5 or other PM2.5 precursors, either alone or in combination with NH3, may be necessary for more substantial air quality improvements. In terms of nitrogen (N) deposition, reductions in NH3 emissions primarily affect NH3 dry deposition, which constitutes approximately two-thirds of reduced nitrogen deposition. Total N deposition declines by 15–18% in source regions depending on the scenario, but national average reductions remain modest (~4%). While the study emphasizes annual estimates, further analyses focusing on finer temporal scales (e.g., daily or seasonal) could provide additional insights into exposure impacts. This research highlights the need for integrated mitigation strategies addressing multiple pollutants to achieve meaningful reductions in air pollution and nitrogen deposition.